Analysis of the Interaction between DNA Aptamers and Cytochrome C on the Surface of Lipid Films and on the MUA Monolayer: A QCM-D Study - Marek Tatarko; Sandro Spagnolo; Martin Csiba; Veronika Šubjaková; Tibor Hianik (Biosensors, 2023)
We analyzed the possibility of the detection of cytochrome c (cyt c) being physically adsorbed on lipid films or covalently bounded to 11-mercapto-1-undecanoic acid (MUA) chemisorbed on the gold layer using quartz crystal microbalance with dissipation monitoring (QCM-D). The negatively charged lipid film composed of a mixture of zwitterionic DMPC and negatively charged DMPG phospholipids at a molar ratio of 1:1 allowed the formation of a stable cyt c layer. Addition of DNA aptamers specific to cyt c, however, resulted in removal of cyt c from the surface. The interaction of cyt c with the lipid film and its removal by DNA aptamers were accompanied by changes in viscoelastic properties evaluated using the Kelvin–Voigt model. Cyt c covalently bound to MUA also provided a stable protein layer already at its relatively low concentrations (0.5 μM). A decrease in the resonant frequency following the addition of gold nanowires (AuNWs) modified by DNA aptamers was observed. The interaction of aptamers with cyt c on the surface can be a combination of specific and non-specific interactions due to electrostatic forces between negatively charged DNA aptamers and positively charged cyt c.